A Rose by any other name - McMyne, Mary (New York, NY : Redhook, 2024)
"England, 1603. Rose Rushe's passion for life runs deep - she laughs too loudly, meddles with astrology and music, and pays no heed to her mother's warnings to guard her reputation. When Rose's father dies and a noble accuses her and her best friend Cecely of witchcraft, they flee to London and make their way as occultists, secretly selling love charms and astrological advice. Their thriving underground business leads them to young noble Henry and playwright Will Shakespeare, and so begins a brief, tempestuous, and powerful romance - one filled with secret longings and deep betrayals"--
Keywords: Shakespeare, William, -- 1564-1616 -- Fiction; Man-woman relationships -- Fiction; Occultists -- Fiction; Great Britain -- History -- Elizabeth, 1558-1603 -- Fiction